Faktor-Faktor yang Mempengaruhi Harga Saham pada Perusahaan LQ45 - Noventin Entelina Panjaitan; Dio Welsen (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study is motivated by the phenomenon of increasing investor interest in stocks included in the LQ45 index. This study aims to test the effect of Liquidity, Leverage, Profitability, Price to Book Value on stock prices. In this study, the variables Liquidity, Leverage, Profitability and Price to Book Value act as independent variables, in addition, the dependent variable used is stock price. The sample in this study was the LQ45 index companies listed on the IDX in 2021-2023 with a total sample of 123 samples. Sample selection was based on the purposive sampling method with criteria and requirements determined by the researcher. The analysis method used in this study is multiple linear regression analysis using the SPSS 25 application. The results of the study show that Liquidity, Leverage, Profitability, Price to Book Value simultaneously affect stock prices. Partially, the Liquidity variable has a negative effect on stock prices while Leverage, Profitability, Price to Book Value does not affect stock prices.